Long‐term outcomes following catheter ablation versus medical therapy in patients with persistent atrial fibrillation and heart failure with reduced ejection fraction. (1st November 2022) - Zakeri, Rosita; Ahluwalia, Nikhil; Tindale, Alexander; Omar, Fatima; Packer, Matthew; Khan, Habib; Baker, Victoria; Honarbakhsh, Shohreh; Earley, Mark J.; Sporton, Simon; Schilling, Richard J.; Jones, David; et al.
Abstract : Aims: The ARC‐HF and CAMTAF trials randomized patients with persistent atrial fibrillation (AF) and heart failure (HF) to early routine catheter ablation (ER‐CA) versus pharmacological rate control (RC). After trial completion, delayed selective catheter ablation (DS‐CA) was performed where clinically indicated in the RC group. We hypothesized that ER‐CA would result in a lower risk of cardiovascular hospitalization and death versus DS‐CA in this population. Methods and results: Overall, 102 patients were randomized (age 60 ± 11 years, left ventricular ejection fraction [LVEF] 31 ± 11%): 52 to ER‐CA and 50 to RC. After 12 months, patients undergoing ER‐CA had improved self‐reported symptom scores, lower New York Heart Association class (i.e. better functional capacity), and higher LVEF compared to patients receiving RC alone. During a median follow‐up of 7.8 (interquartile range 3.9–9.9) years, 27 (54%) patients in the RC group underwent DS‐CA and 34 (33.3%) patients died, including 17 (32.7%) randomized to ER‐CA and 17 (34.0%) randomized to RC. Compared with DS‐CA, a strategy of ER‐CA exhibited similar risk of all‐cause mortality (adjusted hazard ratio [aHR] 0.89, 95% confidence interval [CI] 0.44–1.77, p  = 0.731) and combined all‐cause mortality or cardiovascular hospitalization (aHR 0.80, 95% CI 0.43–1.47, p  = 0.467). However, analyses according to treatment received suggested an association between CA and improved outcomes versus RC (all‐cause mortality: aHR 0.43, 95% CI 0.20–0.91, p  = 0.028; all‐cause mortality/cardiovascular hospitalization: aHR 0.48, 95% CI 0.24–0.94, p  = 0.031). Conclusions: In patients with persistent AF and HF, ER‐CA produces similar long‐term outcomes to a DS‐CA strategy. The association between CA as a treatment received and improved outcomes means there is still a lack of clarity regarding the role of early CA in selected patients. Randomized trials are needed to clarify this question. Abstract : In intention‐to‐treat analyses, early routine catheter ablation (CA) resulted in similar long‐term outcomes to a delayed selective CA strategy in patients with persistent or long‐standing persistent atrial fibrillation (AF) and symptomatic heart failure with reduced ejection fraction (HFrEF) enrolled in the ARC‐HF and CAMTAF clinical trials. Medical therapy refers to pharmacological rate control. Kaplan–Meier survival curves shown for all‐cause death (left) and a composite outcome of all‐cause death or cardiovascular (CV) hospitalization (right). CI, confidence interval; HR, hazard ratio; IQR, interquartile range; NYHA, New York Heart Association.